Raman analysis on methane production from natural gas hydrate by carbon dioxide–methane replacement. (1st January 2015) - Xu, Chun-Gang; Cai, Jing; Lin, Fu-hua; Chen, Zhao-Yang; Li, Xiao-Sen
Abstract: Using CO2 –CH4 (carbon dioxide–methane) replacement to produce CH4 from NGH (natural gas hydrate) is not only a new CH4 production technology but also a direct way to disposal CO2 by CO2 hydrates. Although there are many studies focusing on the mechanism of CH4 replacement in hydrates by CO2, the mechanism of the replacement is still not clear. In this work, the replacement process and hydrate structure change are tracked and investigated by Raman and NMR (nuclear magnetic resonance) spectra. By comprehensively analyzing the Raman and NMR spectra, we infer the mechanism of the replacement and the hydrate structures. Conclusions are drawn as, on one hand, CH4 molecules are fully replaced with the gas–solid interface, but partly replaced in deeply inner hydrates by CO2 molecules; on the other hand, the CO2 hydrate and CH4 hydrate coexist in a type of structure I (sI) and there is no structure transformation during the replacement. The research results are important to further confirm the mechanism of the replacement and reveal factors restraining efficiency of the CH4 production. Highlights: CH4 and CO2 coexist in sI hydrates. Only CH4 molecules in 5 12 6 2 cages are replaced. Replacement includes processes of CH4 hydrate dissociation and CO2 hydrate formation. Gas diffusion in hydrate is a key to replacement efficiency.